Is the cardamom whitefly Kanakarajiella cardamomi (David and Subralllaniam) a vector of Nilgiri Necrosis Virus disease of cardamom Elettaria cardamomum Maton? - KUMARESAN, S SELVAKUMARAN, B VASANTHARAJ DAVID, D (Journal of Spices and Aromatic Crops, 1997)
The vector and mode of transmission of the Nilgiri Necrosis Virus (NNV) disease affecting cardamom. Elettaria cardamomum Matoh is 'unknown so far. More than 70 whitefly borne viral diseases have been reported on cultivated plants and weeds from ttopical and subtropical regions (Cohen 1990). Muniappa (1980) in his critical review listed 65 viral diseases transmitted by whiteflies. The present studies were carried out to determine whether the cardamom whitefly, Kanakarajiella cardamomi (David and Subramaniam), an important pest on cardamom, acts as a vector of the NNV disease.